2012
DOI: 10.48084/etasr.238
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Strength Properties of Palm Kernel Shell Ash Concrete

Abstract: Many researchers have studied the use of agro-waste ashes as constituents in concrete. These agro-waste ashes are siliceous or aluminosiliceous materials that, in finely divided form and in the presence of moisture, chemically react with the calcium hydroxide released by the hydration of Portland cement to form calcium silicate hydrate and other cementitious compounds. Palm kernel shell ash (PKSA) is a by-product in palm oil mills. This ash has pozzolanic properties that enables it as a partial replacement for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Authors in [15] used Rice Husk Ash (RHA) in concrete and concluded that the compressive and tensile strength of the concrete specimens increased 11.8% and 7.31%, respectively when 10% RHA was used and after 28 days of curing. Authors in [16] used Palm Kernel Shell Ash (PKSA) in concrete to assess the compressive strength and discussed that the use of PKSA as a partial replacement for cement in concrete, at lower volume of replacement, enhances the reduction of cement usage in concrete, thereby reducing production cost. Authors in [17] also studied the effect of fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [15] used Rice Husk Ash (RHA) in concrete and concluded that the compressive and tensile strength of the concrete specimens increased 11.8% and 7.31%, respectively when 10% RHA was used and after 28 days of curing. Authors in [16] used Palm Kernel Shell Ash (PKSA) in concrete to assess the compressive strength and discussed that the use of PKSA as a partial replacement for cement in concrete, at lower volume of replacement, enhances the reduction of cement usage in concrete, thereby reducing production cost. Authors in [17] also studied the effect of fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…For the cement pastes, the binders (i.e., CEM I and silica fume) were first blended in the mixer for three minutes before adding water and mixing for another two minutes. The mixes were then poured into oiled molds of size 150×150×150mm 3 , compacted, and covered for 24 hours. The specimens were then removed from the molds and cured in water at a constant 20±2°C temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the increase in cement demand will be met by the use of supplementary cementing materials, in order to reduce the green gas emission. Industrial waste, such as blast furnace slag, fly ash, and silica fume are being used as supplementary cement replacement materials and, recently, agricultural waste is also being used as pozzolanic material in concrete [3]. The size of silica fume is hundreds of times smaller than cement particles, causing decrease to the permeability of concrete.…”
mentioning
confidence: 99%
“…Concrete is the most popular construction material. It may be used alone as mass concrete or with steel as reinforced or pre-stressed concrete [1,2]. Ordinary Portland Cement (OPC), which is the main component of various concrete types, is one of the most common construction materials worldwide.…”
Section: Introductionmentioning
confidence: 99%